Fatin's Diary dalam Panggung Kultur Pop-Religius - Siti Nur Hidayah; Claudia Tevy (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2016)
The development of era demands muslimahs to take roles without leaving their identities. When they became career women, they were asked to work outside their houses. How if the women want to keep their faith and obey the Islamic rules by keeping their aurat with jilbab (veil)? Will jilbab disturb their activities when working? How if their working environments do not accept them? The paper discusses the relationship between the activities of women with hijab and their adaptation by analyzing Fatins Hijab Diary. With Scheiders analysis, it can be concluded that Fatin Shidqia Lubis, as an entertainer and public figure has conducted the adaptation process toward her working environment in order to be exist in it without leaving her identity as a muslimah who holds the hijabs principals. The process that has been successfully passed by Fatin shows that jilbab is not an obstruction for women who want to work and be famous.